"TPACK Stories": Schools and School Districts Repurposing a Theoretical Construct for Technology-Related Professional Development. Issue 1 (3rd April 2017) - Harris, Judith B.; Hofer, Mark J.
Abstract: TPACK (Koehler & Mishra, 2008 ), a theoretical construct that describes the knowledge that teachers use to teach with digital tools and resources, has flourished in university-based teacher education and research. Increasingly, K–12 schools and districts have also appropriated TPACK in their professional development efforts. This study of seven schools and districts explored how the TPACK construct was understood and used in these K–12 organizations. Study results revealed the importance of context and professional culture in appropriating the construct; the use of TPACK as a way to connect disparate professional development initiatives; TPACK conceptualized as applied knowledge; and how educational leaders' beliefs about professional development shape how TPACK is understood and enacted. (Keywords: TPACK, TPCK, professional development, context)